Analysis of One-Dimensional Consolidation for Unsaturated Soils under Piecewise Cyclic Loading - Yuanchun Huang; Sidong Shen; Lei Wang; Tianyi Li; Xianlei Fu (Advances in Civil Engineering)
This paper studies the one-dimensional (1D) consolidation behavior for unsaturated stratum subjected to piecewise cyclic loading. Combined with the widely accepted consolidation theory of unsaturated soils, a semianalytical method was employed to investigate the consolidation of unsaturated foundation considering piecewise cyclic loading in the Laplace domain. Furthermore, the reduced solutions were produced to perform the verification work accompanied by the results in the existing literature. Finally, a case study was conducted to explore the consolidation characteristics under piecewise cyclic loading (i.e., triangular and trapezoidal cyclic loadings). Parametric studies were carried out by variations of excess pore pressures and settlement against the ratio of air-water permeability coefficients, depth, and loading parameters. The research proposed in this paper can provide theoretical basis for the ground treatment of unsaturated soils, especially for rationally accelerating consolidation or avoiding sudden settlement.